Dynamics of Exchange Rates in Selected Emerging Markets in Risk-on/Risk-off Periods - Ivanov, David; Brůna, Karel, 1973-; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
This thesis focuses on exchange rates dynamics in Mexico, Turkey and South Korea. We examine the capital flow development in mentioned countries and currency dynamics of the Mexican Peso, Turkish Lira and Korean Won. The main goal of the paper is to evaluate the performance of these currencies in risk-on and risk-off episodes on a sample period from 1997 until 2016. We use analysis and comparison as a methodology for this paper, emphasizing on the relationship and causality between capital flow and exchange rates. We shall reveal that the examined currencies depreciate in risk-off periods and only the Korean Won appreciates in risk-on periods.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses